Stołówki w przestrzeni socjalistycznego miasta - Milewska, Monika (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2021)
In the People’s Republic of Poland a workplace, along with its social infrastructure meeting most of the basic needs of employees, was to be an alternative space to the city. Canteens, which were to feed the employees rationally, increasing work efficiency and freeing women from household chores, played a key role here. This project failed, partly also for reasons related to the space of the canteens themselves: they were unaesthetic, unsanitary and inaccessible to family members
24 cm
Keywords: canteens; food; workers; People’s Republic of Poland

Wyciąż - Nowa Huta : sprawozdanie Kazimierza Bielenina z prac wykopaliskowych na cmentarzysku - Sawicki, Ludwik (1893–1972); Bielenin, Kazimierz (1923–2011) (1951)
Materiały archiwalne należące do spuścizny po prof. Ludwiku Sawickim
Keywords: Nowa Huta (Cracow, Poland); rescue excavations; Cracow, małopolskie voivodeship (Poland)

Wyniki analiz tkanin wykopaliskowych z Nowej Huty-Mogiły - Tumalewiczowa, Weronika (1909–1976) (Zakład Narodowy im.Ossolińskich, 1959)
ill. ; 29 cm
Keywords: Nowa Huta (Cracow, Poland); archaeological textiles; Cracow, małopolskie voivodeship (Poland)

Zboża chlebowe, rośliny strączkowe i konopie z okresu lateńskiego i rzymskiego z okolic Krakowa - Moldenhawer, Konstanty (1889–1962) (Zakład Narodowy im.Ossolińskich, 1959)
ill. ; 29 cm
Keywords: La Tène-Roman period -- Poland; Nowa Huta (Cracow, Poland); paleobotanical researches; cultivated plants; plant species; Wyciąże, Nowa Huta (Cracow, Poland)

„Nowohuckie podwórka” – od podwórka. Spojrzenie etnologa - Baniowska-Kopacz, Ewa (Instytut Archeologii i Etnologii PAN, 2019)
The article discusses the topic of spaces adjacent to houses in the oldest area of Nowa Huta, a district of Cracow established in the middle of the 20th century. These spaces are mostly courtyards, and especially household gardens located in those courtyards, e.g. at the front walls of houses, between the entryways or in the backyards, directly under apartment windows. Such gardens – separated spaces established and farmed by the residents of Nowa Huta – provide a basis for presenting the local community. The article constitutes an attempt at analysing the community through those domesticated patches of land, transformed by the residents’ actions into a place, i.e. a tamed space endowed with individual features and constituting a part of the life of individual residents and the community as a whole
24 cm
Keywords: space; place; residences; rootedness; backyard; Nowa Huta gardens; Cracow-Nowa Huta; Poland

Fibula palczasta z Nowej Huty-Mogiły - Hachulska-Ledwos, Renée (Zakład Narodowy im.Ossolińskich, 1966)
ill. ; 29 cm
Keywords: 6th c. -- Poland; finger-shaped fibulae; Cracow-Nowa Huta-Mogiła (Poland)

Materiały kamienne z przydomowej pracowni krzemieniarskiej z jamy 1 na stanowisku II w Nowej Hucie-Pleszowie - Cabalska, Maria (1919–2000) (Zakład Narodowy im.Ossolińskich, 1964)
ill. ; 29 cm
Keywords: Neolithic -- Poland; Pleszów (Nowa Huta, Cracow, Poland); Neolithic stone working; Neolithic flint workshops; Neolithic stone objects

Materiały ceramiczne z przydomowej pracowni krzemieniarskiej z jamy 1 na stanowisku II w Nowej Hucie-Pleszowie - Godłowska, Marta (Zakład Narodowy im.Ossolińskich, 1964)
ill. ; 29 cm
Keywords: Neolithic -- Poland; Neolithic flint working; Neolithic flint workshops; Pleszów (Nowa Huta, Cracow, Poland)

Antropomorficzna główka gliniana z Nowej Huty-Pleszowa - Rachwaniec, Andrzej (Zakład Narodowy im. Ossolińskich, 1976)
P. 63-76 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Neolithic -- Poland; Neolithic anthropomorphic figurines; anthropomorphic head of clay; Nowa Huta-Pleszów (Cracow, Poland); Cracow (Poland)

Grób kultury lendzielskiej z Krakowa-Nowej Huty, stanowisko 17 (Pleszów) - Godłowska, Marta (Zakład Narodowy im. Ossolińskich, 1978)
P. 21-30 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Neolithic -- Poland; Lengyel culture; Lengyel culture graves; Lengyel culture grave goods; Kraków-Nowa Huta (Poland)

Wyniki badań mineralogicznych ceramiki "białej" ze stanowisk w Krakowie-Nowej Hucie - Pawlikowski, Maciej (Polska Akademia Nauk. Instytut Archeologii i Etnologii, 2000)
P. 419-433, [2] leaves of photos : tables ; 25 cm
English summary
Bibliography p. 431
Keywords: early Middle Ages -- Poland; early medieval white pottery; mineralogical analysis; Nowa Huta (Cracow, Poland); Cracow (Poland)

Radial Ware culture, classical phase : Cracow-Nowa Huta, Site 17 (Pleszów), settlement - Godłowska, Marta; Gluza, Irena (Polska Akademia Nauk. Instytut Historii Kultury Materialnej, 1989)
ill. ; 29 cm
Keywords: Eneolithic -- Poland; Baden culture; Baden culture settlement; absolute chronology; radiocarbon dating; Cracow-Nowa Huta (Poland)

Lengyel Culture, Modlnica Phase : Cracow-Nowa Huta, Site 62 (Mogiła), Pit 416 - Godłowska, Marta; Gluza, Irena (Polska Akademia Nauk. Instytut Historii Kultury Materialnej, 1989)
ill. ; 29 cm
Keywords: Neolithic -- Poland; Lengyel culture; Modlnica group; absolute chronology; radiocarbon dating; Cracow-Nowa Huta-Mogiła (Poland)

Ziemianki-spichlerze z okresów lateńskiego i rzymskiego odkryte na terenach budowy Nowej Huty - Buratyński, Stanisław (1908–1994) (Zakład Narodowy im.Ossolińskich, 1959)
ill. ; 29 cm
Keywords: La Tène-Roman period -- Poland; Nowa Huta (Cracow, Poland); La Tène-Roman basin houses; storage pits; Cracow, małopolskie voivodeship (Poland)

Sprawozdania Archeologiczne T. 25 (1973), Omówienia i recenzje - Szymański, Wojciech (1932– ). Reviewer (Zakład Narodowy im. Ossolińskich, 1973)
R. Hachulska-Ledwos, Wczesnośredniowieczna osada w Nowej Hucie-Mogile, Materiały Archeologiczne Nowej Huty, t. 3, Kraków 1971
P. 348-353 ; 25 cm
Bibliographical footnotes
Keywords: early Middle Ages -- Poland; early medieval settlements; early medieval pottery; Nowa Huta-Mogiła (Cracow, Poland); Cracow (Poland)

Analiza technologiczna wybranych fragmentów ceramiki kultury lendzielskiej ze stan. 17 w Nowej Hucie-Pleszowie - Wirska-Parachoniak, Maria (Zakład Narodowy im. Ossolińskich, 1976)
P. 79-87 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Neolithic -- Poland; Lengyel culture; Lengyel culture pottery; technological analysis of pottery; Nowa Huta-Pleszów (Cracow, Poland); Cracow (Poland)

Sprawozdania Archeologiczne T. 28 (1976), Sesje i konferencje - Polska Akademia Nauk. Instytut Archeologii i Etnologii; Polska Akademia Nauk. Instytut Historii Kultury Materialnej (Zakład Narodowy im. Ossolińskich, 1976)
Seminarium "Starosłowiańskie osadnictwo w Nowej Hucie-Krakowie na tle aktualnych badań nad "praską" prowincją kulturową". Kraków, 9-11 października 1974
P. 332-334 ; 25 cm
Bibliographical footnotes
Keywords: early Middle Ages -- Poland; archaeological conferences; Prague-Korchak culture; Slavs (peoples); Slavs settlement -- Poland; Nowa Huta (Cracow, Poland); Cracow (Poland)

Uwagi o antropomorficznej główce glinianej z Nowej Huty-Pleszowa - Kaczanowska, Małgorzata (Zakład Narodowy im. Ossolińskich, 1982)
P. 13-18 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Neolithic -- Poland; Neolithic anthropomorphic figurines; anthropomorphic head of clay; mineralogical and petrographic analysis; Nowa Huta-Pleszów (Cracow, Poland); Cracow (Poland)

Analiza mikroskopowa zabytków z grobu kultury lendzielskiej (nr 1325) na stanowisku 17 w Pleszowie (Kraków-Nowa Huta) - Drobniewicz, Barbara (Zakład Narodowy im. Ossolińskich, 1978)
P. 31-32 ; 25 cm
English summary
Keywords: Neolithic -- Poland; Lengyel culture; Lengyel culture graves; Lengyel culture grave goods; microscopic analysis of finds; Kraków-Nowa Huta (Poland)

Z problematyki badawczej osadnictwa neolitycznego w Pleszowie-Nowej Hucie - Kulczycka-Leciejewiczowa, Anna (Zakład Narodowy im. Ossolińskich, 1969)
P. 479-481 ; 25 cm
Keywords: Neolithic -- Poland; Lengyel culture; chronology of the Lengyel culture; Lengyel culture pottery; Nowa Huta-Pleszów (Cracow, Poland); Cracow (Poland)

Nowe znalezisko konopi (Cannabis sativa L.) z okresu przedpiastowskiego w Polsce - Wasylikowa, Krystyna (Zakład Narodowy im. Ossolińskich, 1969)
P. 465-468 : ill. ; 25 cm
English summary
Keywords: early Middle Ages -- Poland; plant remains; paleobotanical analysis; cultivated plants; hemp (cultivated plant); Nowa Huta (Cracow, Poland); Cracow (Poland)

Sprawozdanie z badań wykopaliskowych w Zesławicach (Nowa Huta) w latach 1953 - 1955 - Zemełka, Stanisław (Zakład im. Ossolińskich, 1957)
P. 31-38 : ill. ; 25 cm
English, Russian summaries
Bibliographical footnotes
Keywords: Neolithic-Bronze Age -- Poland; Neolithic-Bronze Age cultures; Baden culture settlements; Neolithic graves; Neolithic pottery; Zesławice (Nowa Huta, Poland)

Folklor w etnologji - Gomme, George Laurence (1853–1916) (Druk. K. Kowalewskiego, 1901)
[2], 194, [2] p. : errata ; 21 cm
Bibliographical footnotes
Keywords: folklore; ethnology

Elementy kultury Gáva w rejonie Krakowa-Nowej Huty - Bazielich, Maria (Zakład Narodowy im. Ossolińskich, 1984)
P. 317-349 : ill. ; 25 cm
Bibliography p. 344-347
English summary
Keywords: Bronze Age -- Poland; Nowa Huta (Cracow, Poland); Gáva culture; Gáva culture pottery; Gáva culture pottery -- typology; Cracow, małopolskie voivodeship (Poland)

Zagadkowe znaki na dnie naczynia wczesnorzymskiego z Wyciąży w pow. krakowskim - Buratyński, Stanisław (1908–1994) (Zakład Narodowy im.Ossolińskich, 1958)
ill. ; 29 cm
Keywords: early Roman period -- Poland; Wyciąże, Nowa Huta (Cracow, Poland); early Roman period pottery; potter's marks on early Roman pottery; Cracow, małopolskie voivodeship (Poland)